Analisis Kinerja Pengurus Komunitas Basis Gerejawi Paroki Santo Fransiskus Asisi Di Kota Batam - Evy Puspitosari; Sanga, Laurensius Dihe; Tamba, Imelda (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2022)
ABSTRAK The realitas give a some indication that motivation and empowerment become a important. So in this the church Katolik. For that i can analisis with the Cuantitative methode to see about the situasion in church Katolik St. Fransiskuas Asisi – Batam. This research aims to determine the influence of empowerment, motivation and leadership on the performance of the management of the Ecclesiastical Base Community (KBG) of St. Francis Asisi Parish in Batam City. There were 90 respondents, the data was processed using SPSS 26. From the results of data processing, it was obtained that the empowerment variable has a calculated tcount 2,828 > ttable 1,662 with a significance value of 0,006 < 0,05, so empowerment has a positive and significant influence on the performance of KBG management. The motivation variable has a calculated tcount 2,939 > ttable 1,662 with a significance level of 0,004 < 0,05, then motivation has a positive and significant influence on the performance of KBG management, and the leadership variable has a calculated tcount 2,795 > ttable 1,662 with a significance level of 0,006 < 0,05, then leadership has a positive and significant influence on the performance of KBG management. Based on the results of the coefficient of determination test, an Adjusted R Square value of 0,531 was obtained, meaning that the variables of empowerment, motivation and leadership influenced the performance of KBG management by 53.1%, and the remaining 46.9% was influenced by other variables outside this research.